Nahwu Analysis Activities in Reading the Text of Natsar Al-Barzanji and Its Effect on The Ability of Reading Arabic Texts - Rina Septiani; Riska Hermina Rahmawati; Risna Nurul Insani (Indonesian Journal of Arabic Studies, 2023)
Purpose: This study, conducted at Al-Mardhiyyah Al-Islamiyyah Islamic Boarding School, investigates the impact of incorporating nahwu (Arabic syntax) analysis into the traditional reading of Natsar al-Barzanji on students' Arabic reading abilities. Originally part of the "marhabanan" tradition, the reading of Natsar al-Barzanji has been transformed into an educational tool to deepen students' comprehension of Arabic language and nahwu concepts. The objective of this research is to ascertain whether a focused approach to nahwu analysis can effectively enhance students' proficiency in reading Arabic texts. Design/ methods/approach: Employing a descriptive research methodology, the study utilized both qualitative and quantitative data analyses to evaluate the effectiveness of this approach. The quantitative data was collected through assessments measuring students' performance in nahwu analysis and their Arabic reading skills. Findings: Results indicated a significant improvement in Arabic reading abilities among students. The highest score in nahwu analysis was 99, with the lowest at 42, and an average score of 85.66 (standard deviation of 5.59). In Arabic text reading, the highest score recorded was 96, the lowest at 60, with an average of 82.47 (standard deviation of 8.89). The correlation coefficient of 0.66 suggests a meaningful positive impact of nahwu analysis on Arabic reading proficiency. Research implications: Â This research demonstrates the beneficial role of integrating linguistic analysis into language education, particularly in enhancing reading abilities. It contributes to the field by highlighting how syntax-focused activities can significantly improve linguistic proficiency. The findings offer valuable insights for educators and curriculum developers in Arabic language education, suggesting that incorporating nahwu analysis can effectively bolster students' comprehension and fluency in Arabic.